Evidence of resilience capacity in farmers' narratives: Accounts of robustness, adaptability and transformability across five different European farming systems. (December 2021) - Nicholas-Davies, Phillipa; Fowler, Susan; Midmore, Peter; Coopmans, Isabeau; Draganova, Mariana; Petitt, Andrea; Senni, Saverio
Abstract: Understanding how farmers perceive and manage critical decision points in response to challenges and opportunities can help to develop effective support for resilient European farming systems. Individual narratives of farm stories provide insight into important management changes over time and the context in which they were made. We analyse 46 personal narratives from family farms across a range of farming systems in five European countries and use comparative thematic analysis to identify these change drivers and responses to them. Pressures within the family and the farming business (caused by health problems or intergenerational transition) were more important to narrators than external drivers such as extreme weather events and price fluctuations. The latter, perceived as outside the control of the farmer, were regarded as background noise requiring no significant business changes. While different resilience responses (robustness, adaptation, and transformation) were revealed, these categories were fluid depending on individual capacities, farm resources and the overall setting. Farms could appear robust but, over time, small changes in management could cumulate to adapt or even transform the management and scope of the business. Policy-related conclusions include a need for more flexible, tailored farm support and more coherent long-term strategies to manage intergenerational transition on farms. Highlights: Internal drivers of change were most important in family farm businesses. Succession process impacts resilience and sustainability of family farm businesses. Adaptive capacities on a spectrum, rather than discrete categorical variables. Robustness observed at a point in time can in fact be creeping change. Creeping change can result in substantial change to the system – slow adaptation.